Compositionally tuned magnetron co-sputtered PtxNi100-x alloy as a cathode catalyst for proton exchange membrane fuel cells - Khalakhan, Ivan; Supik, Lukáš; Vorokhta, Mykhailo; Yakovlev, Yurii; Dopita, Milan; Sandbeck, Daniel; Cherevko, Serhiy; Veltruská, Kateřina; Matolínová, Iva (Applied Surface Science, 2020)
In this study, PtxNi100-x (0 ≤ x ≤ 100) alloy catalysts were prepared using magnetron co-sputtering in order to reveal the correlation between their composition and catalytic properties as a cathode in proton exchange membrane fuel cells (PEMFCs). Fine power adjustment on magnetrons allowed to deposit alloys with precise composition and at the same time with identical thickness of 10 nm and similar morphologies. The powerful surface characterization techniques such as atomic force microscopy (AFM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray reflectivity (XRR) and X-ray photoelectron spectroscopy (XPS) were applied to thoroughly investigate the catalytic layers. The desired composition of the films was confirmed by EDX and XRD results. All deposited layers showed similar morphologies with vertical and horizontal roughness of 0.35 nm and 6 nm, respectively. XRD confirmed the alloy nature of the films with one crystalline phase of the fcc PtNi. The PtxNi100-x alloys showed significant enhancement of specific power (SP) comparing to the pure Pt in PEMFC. Particularly, the Pt25Ni75 sample exhibited the highest SP of 24 kW/g(Pt). This catalyst showed a 2- and almost 10-fold improvement in SP with respect to the Pt film and commercial nanopowder Pt catalyst, respectively.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Bimetallic catalyst; Fuel cell; Magnetron sputtering; Pt-Ni; Thin film

Effect of Ionic Liquid Modification on the ORR Performance and Degradation Mechanism of Trimetallic PtNiMo/C Catalysts - George, Michael; Zhang, Gui-Rong; Schmitt, Nicolai; Brunnengraeber, Kai; Sandbeck, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Etzold, Bastian J.M. (ACS Catalysis, 2019)
Ionic liquids (ILs) modification, following the concept of "solid catalyst with ionic liquid layer (SCILL)", has been demonstrated to be an effective approach to improving both activity and stability of Pt-based catalysts for the oxygen reduction reaction. In this work, the SCILL concept has been applied to a trimetallic PtNiMo/C system, which has been documented recently to be significantly advantageous over the benchmark PtNi-based catalysts for oxygen reduction. To achieve this, two hydrophobic ILs ([BMIM][NTF2] and [MTBD][BETI]) were used to modify PtNiMo/C with four IL-loading amounts between 7 and 38 wt %. We found that the Pt mass activity (@0.9 V) could be improved by up to 50% with [BMIM][NTF2] and even 70% when [MTBD][BETI] is used. Exceeding a specific IL loading amount, however, leads to a mass transport related activity drop. Moreover, it is also disclosed that both ILs can effectively suppress the formation of nonreactive oxygenated species, while at the same time imposing little effect on the electrochemical active surface area. For a deeper understanding of the degradation mechanism of pristine and IL modified PtNiMo/C, we applied identical location transmission electron microscopy and in situ scanning flow cell coupled to inductively coupled plasma mass spectrometry techniques. It is disclosed that the presence of ILs has selectively accelerated the dissolution of Mo and eventually results in a more severe degradation of PtNiMo/C. This shows that future research needs to identify ILs that prevent the Mo dissolution to leverage the potential of the IL modification of PtNiMo catalysts.
CRIS-Team Scopus Importer:2019-09-27
Keywords: electrocatalysis; ionic liquid; metal dissolution; oxygen reduction; PtNiMo catalyst; stability

Evolution of the PtNi Bimetallic Alloy Fuel Cell Catalyst under Simulated Operational Conditions - Khalakhan, Ivan; Bogar, Marco; Vorokhta, Mykhailo; Kúš, Peter; Yakovlev, Yurii; Dopita, Milan; Sandbeck, Daniel; Cherevko, Serhiy; Matolínová, Iva; Amenitsch, Heinz (ACS Applied Materials and Interfaces, 2020)
Comprehensive understanding of the catalyst corrosion dynamics is a prerequisite for the development of an efficient cathode catalyst in proton-exchange membrane fuel cells. To reach this aim, the behavior of fuel cell catalysts must be investigated directly under reaction conditions. Herein, we applied a strategic combination of in situ/online techniques: in situ electrochemical atomic force microscopy, in situ grazing incidence small angle X-ray scattering, and electrochemical scanning flow cell with online detection by inductively coupled plasma mass spectrometry. This combination of techniques allows in-depth investigation of the potential-dependent surface restructuring of a PtNi model thin film catalyst during potentiodynamic cycling in an aqueous acidic electrolyte. The study reveals a clear correlation between the upper potential limit and structural behavior of the PtNi catalyst, namely, its dealloying and coarsening. The results show that at 0.6 and 1.0 VRHE upper potentials, the PtNi catalyst essentially preserves its structure during the entire cycling procedure. The crucial changes in the morphology of PtNi layers are found to occur at 1.3 and 1.5 VRHE cycling potentials. Strong dealloying at the early stage of cycling is substituted with strong coarsening of catalyst particles at the later stage. The coarsening at the later stage of cycling is assigned to the electrochemical Ostwald ripening process.
CRIS-Team Scopus Importer:2020-04-28
Keywords: bimetallic catalyst; dealloying; degradation; fuel cells; in situ electrochemical atomic force microscopy (EC-AFM); in situ grazing incidence small angle X-ray scattering (GISAXS); Ostwald ripening

Interplay among Dealloying, Ostwald Ripening, and Coalescence in Pt XNi100- XBimetallic Alloys under Fuel-Cell-Related Conditions - Bogar, Marco; Yakovlev, Yurii; Sandbeck, Daniel; Cherevko, Serhiy; Matolínová, Iva; Amenitsch, Heinz; Khalakhan, Ivan (ACS Catalysis, 2021)
Platinum-based bimetallic alloys have been largely investigated during the last few years as a valid alternative to bare Pt cathode catalysts for proton-exchange membrane fuel cells (PEMFCs) to improve their cost-efficiency. Nonetheless, Pt bimetallic alloys are characterized by a reduced stability, which is poorly understood at a fundamental level. It is thus essential to describe the entire chain of interconnected degradation mechanisms to formulate a comprehensive model of catalyst degradation that will help interpret bimetallic alloy behavior in real complex fuel cell systems. By combining in situ inductively coupled plasma mass spectroscopy, in situ grazing-incidence small-angle X-ray scattering, and ex situ scanning electron microscopy, we have studied the morphological evolution of PtXNi100-X model catalysts with different Ni contents (ranging from 0 to 75%) undergoing potentiodynamic cycling to two different upper potentials mimicking the different operational conditions of a PEMFC: 1.0 and 1.3 VRHE. Data analysis allowed us to develop a methodology to distinguish the influence of Ni dissolution, particle coalescence, and Ostwald ripening on particle size distribution and interparticle distance and to realize time-dependent interplay maps to highlight the timeframe in which the aforementioned phenomena are prevailing or coexisting. Results show that Ni dissolution is the only phenomenon inducing morphological evolution when the lower upper potential is chosen. On the contrary, at 1.3 VRHE, Ni dissolution is rapidly overcome by particle coalescence at first and by Ostwald ripening in the later stages of the investigated time range. The onset of every phenomenon was found to occur earlier in time for larger values of Ni concentrations.
CRIS-Team Scopus Importer:2021-09-17
Keywords: bimetallic catalyst dealloying; degradation; fuel cells; in situ grazing-incidence small-angle X-ray scattering; Ostwald ripening; particle coalescence

Model electrocatalysts for the oxidation of rechargeable electrofuels - carbon supported Pt nanoparticles prepared in UHV - Stumm, Corinna; Kastenmeier, Maximilian; Waidhas, Fabian; Bertram, Manon; Sandbeck, Daniel; Bochmann, Sebastian; Mayrhofer, Karl; Bachmann, Julien; Cherevko, Serhiy; Brummel, Olaf; Libuda, Jörg (Electrochimica Acta, 2021)
Isopropanol (IPA) can be used as a rechargeable electrofuel. In this approach, IPA is oxidized to acetone (ACE) in a direct alcohol fuel cell and the formed ACE is subsequently back-converted to IPA in a heterogeneously catalyzed process. To study the electrochemical reaction mechanisms of the IPA oxidation at the molecular level, appropriate and well-defined model electrocatalysts are necessary. In this work we prepare such model electrocatalysts by surface science methods in ultra-high vacuum (UHV). The catalysts consist of well-defined platinum nanoparticles on carbon supports. As carbon support, we use flat highly ordered pyrolytic graphite (HOPG) and thin (20 nm) magnetron sputtered carbon films on a polycrystalline gold substrate. In a first step, we characterize the model electrocatalysts and investigate their stability in-situ with complementary methods, i.e. by electrochemical scanning tunneling microscopy (EC-STM), electrochemical on-line inductively coupled plasma mass spectrometry (ICP-MS) and CO stripping experiments followed by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We determined a stability window ranging from -0.65 VRHE to 1.15 VRHE for both sample types, independent of the presence or absence of IPA in the electrolyte. In the second step, we study the oxidation of IPA on tPt nanoparticles using differential electrochemical mass spectrometry (DEMS) and EC-IRRAS. The onset of IPA oxidation is observed at 0.3 VRHE. ACE is formed with high selectivity, while we identify traces of CO2 as the only side-product formed at higher potentials. However, we do not observe any formation of adsorbed CO. A direct comparison of these results with previous work on Pt(111) suggests that low coordinated Pt sites and size effects play a subordinate role for IPA oxidation on Pt electrocatalysts.
CRIS-Team Scopus Importer:2021-07-02
Keywords: 2-propanol; Carbon support; In-situ electrochemical methods; Isopropanol oxidation; Isopropyl alcohol; Model catalysis; Platinum nanoparticles

Particle Size Effect on Platinum Dissolution: Considerations for Accelerated Stability Testing of Fuel Cell Catalysts - Sandbeck, Daniel; Secher, Niklas Morch; Speck, Florian; Sorensen, Jakob Ejler; Kibsgaard, Jakob; Chorkendorff, Ib; Cherevko, Serhiy (ACS Catalysis, 2020)
Polymer electrolyte membrane fuel cells (PEMFCs) are highly attractive for use in electric vehicles. In PEMFCs, small particle sizes of the Pt catalyst are required to increase Pt utilization, which lower costs and also increase Pt dispersion, which itself minimizes O-2 mass transport losses. Reducing the particle size improves both the utilization and dispersion; however, stability of small particle sizes is an issue. Pt dissolution, as one of the major degradation mechanisms of PEMFC catalyst layers, is predicted to depend on the particle size. The particle size cannot be independently varied from loading in commercial Pt/C materials that have been used in numerous studies employing accelerated stability tests (ASTs). Therefore, in the study presented here, the Pt particle diameter was varied from 2 to 10 nm by depositing mass-selected nanoparticles on a flat glassy carbon substrate using magnetron sputtering. This allows exclusive control over particle density (interparticle distance) and particle size, which becomes difficult even with advanced synthetic techniques for applied Pt/C materials. Additionally, effects of the 3D porous support are eliminated. These model systems were subjected to an aggressive AST in order to cause significant Pt dissolution, which was monitored online using the scanning flow cell coupled to an inductively coupled plasma mass spectrometer. The results uncover a previously overlooked phenomenon: two competing trends in dissolution from (1) particle passivation caused by particle sizedependent shifts on oxophilicity and (2) electrochemically active surface area. Therefore, crucial impacts of the particle size on degradation may be overlooked in a variety of electrochemical studies, which compare catalytic materials. Finally, suggestions are given for improved ASTs for dissolution, which provide insights into the intrinsic stability of Pt nanoparticles toward dissolution.
CRIS-Team WoS Importer:2020-06-26

Particle Size Effect on Platinum Dissolution: Practical Considerations for Fuel Cells - Sandbeck, Daniel; Inaba, Masanori; Quinson, Jonathan; Bucher, Jan; Zana, Alessandro; Arenz, Matthias; Cherevko, Serhiy (ACS Applied Materials and Interfaces, 2020)
The high costs of polymer membrane electrolyte fuel cells (PEMFCs) remain a roadblock for a competitive market with combustion engine vehicles. The PEMFC costs can be reduced by decreasing the size of Pt nanoparticles in the catalyst layer, thereby increasing the Pt dispersion and utilization. Furthermore, high-power performance loss due to O2 transport resistance is alleviated by decreasing the particle size and increasing dispersion. However, firm conclusions on how Pt particle size impacts durability remain elusive due to synthetic difficulties in exclusively varying single parameters (e.g., particle size and loading). Therefore, here the particle size of Pt nanoparticles was varied from 2.0 to 2.8 and 3.7 nm while keeping the loading constant (30 wt %) on a Vulcan support using the two-step surfactant-free toolbox method. By studying the electrochemical dissolution in situ using online inductively coupled plasma mass spectrometry (online ICP-MS), mass-specific dissolution trends are revealed and are attributed to particle-size-dependent changes in electrochemically active surface area. Such degradation trends are critical for the start/stop of PEMFCs and currently require the implementation of potential control systems in consumer vehicles. Additionally, shifts in the onset of anodic dissolution and also oxidation to more negative potentials with decreasing particle size were observed. These results indicate a similar mechanism of anodic dissolution related to place-exchange when moving from extended polycrystalline Pt to nanoparticle scales. The negative shifts in the onset as the particle size decreases highlight a practical limitation for PEMFCs during load/idle conditions: without further material improvements, which inhibit Pt dissolution, reduction in costs and improvement in high-power performance via increased Pt utilization and dispersion will not be possible by decreasing particle sizes further.
CRIS-Team Scopus Importer:2020-06-19
Keywords: degradation; electrocatalysis; fuel cells; ORR; particle size; Pt dissolution; stability; toolbox

Structure dependency of the atomic-scale mechanisms of platinum electro-oxidation and dissolution - Fuchs, Timo; Drnec, Jakub; Calle-Vallejo, Federico; Stubb, Natalie; Sandbeck, Daniel; Ruge, Martin; Cherevko, Serhiy; Harrington, David A.; Magnussen, Olaf M. (Nature Catalysis, 2020)
Platinum dissolution and restructuring due to surface oxidation are primary degradation mechanisms that limit the lifetime of platinum-based electrocatalysts for electrochemical energy conversion. Here, we have studied well-defined Pt(100) and Pt(111) electrode surfaces by in situ high-energy surface X-ray diffraction, online inductively coupled plasma mass spectrometry and density functional theory calculations to elucidate the atomic-scale mechanisms of these processes. The locations of the extracted platinum atoms after Pt(100) oxidation reveal distinct differences from the Pt(111) case, which explains the different surface stability. The evolution of a specific oxide stripe structure on Pt(100) produces unstable surface atoms that are prone to dissolution and restructuring, leading to one order of magnitude higher dissolution rates. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-09-04

The Dissolution Dilemma for Low Pt Loading Polymer Electrolyte Membrane Fuel Cell Catalysts - Sandbeck, Daniel; Secher, Niklas Morch; Inaba, Masanori; Quinson, Jonathan; Sorensen, Jakob Ejler; Kibsgaard, Jakob; Zana, Alessandro; Bizzotto, Francesco; Speck, Florian D.; Paul, Michael T.Y.; Dworzak, Alexandra; Dosche, Carsten; et al. (Journal of The Electrochemical Society, 2020)
Cost and lifetime currently hinder widespread commercialization of polymer electrolyte membrane fuel cells (PEMFCs). Reduced electrode Pt loadings lower costs; however, the impact of metal loading (on the support) and its relation to degradation (lifetime) remain unclear. The limited research on these parameters stems from synthetic difficulties and lack of in situ analytics. This study addresses these challenges by synthesizing 2D and 3D Pt/C model catalyst systems via two precise routes and systematically varying the loading. Pt dissolution was monitored using on-line inductively coupled plasma mass spectrometry (on-line-ICP-MS), while X-ray spectroscopy techniques were applied to establish the oxidation states of Pt in correlation with metal loading. Dissolution trends emerge which can be explained by three particle proximity dependent mechanisms: (1) shifts in the Nernst dissolution potential, (2) redeposition, and (3) alteration of Pt oxidation states. These results identify engineering limitations, which should be considered by researchers in fuel cell development and related fields.
CRIS-Team Scopus Importer:2020-12-11